Blood pressure by age, gender, height, and socioeconomic level in school populations in Cali, Colombia (Colombia Medica, 2012)
Introduction: Blood pressure (BP) is a vital sign that should be recorded in children and adolescents. Studies have shown that hypertension in children can lead to adult cardiovascular diseases, which are the leading cause of death in many countries, including Colombia. The aim of this paper was to show the blood pressure data in a school population, 7 to 18 years of age in the city of Cali. Methods: We performed a cross-sectional study to assess risk factors for chronic diseases in a school population of Cali, Colombia, which included anthropometry, blood chemistry, physical work capacity, oral health, diet, and BP. Two pediatricians registered BP by auscultatory method in both arms according to standard method. BP data, their relationship with age, gender, height, body mass index, socioeconomic status, and salt intake were reported for this student population. Results: A total of 2807 students from different Educational institutions in the urban area of Cali were evaluated. Some 92.2% of the school population had normal BP with values below the 90th percentile, 3.8% had blood pressure between 90 to 95th percentiles or prehypertension, and 3.2% were hypertensive with blood pressure above the 95th percentile for age, gender, and height percentiles according to standards. Systolic and diastolic blood pressure increases with age, height, and in males the values are slightly higher. No significant differences were found in systolic and diastolic BP regarding socioeconomic status. There was no difference between right and left arm BP. Higher sodium intake in diet and body mass index increase systolic BP levels. Conclusions: The data found agree with those reported in the literature. Socioeconomic level does not influence blood pressure values in the population studied.